2014
DOI: 10.1111/bjet.12209
|View full text |Cite
|
Sign up to set email alerts
|

Increasing performance by differentiated teaching? Experimental evidence of the student benefits of digital differentiation

Abstract: This paper explores the effect of digital differentiation on student performance using a randomized experiment. The experiment is conducted in a second year biology class among 115 prevocational students in the Netherlands. Differentiation allowed students in the treatment group to work at three different levels. The results show that there is a significant effect of digital differentiation on the posttest score. This effect is robust to adding covariates such as students' ability, grade repetition, age, gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
4
13
0
Order By: Relevance
“…Students were exposed to three experiments in a row and hence it cannot be excluded that some transfer may have occurred. However, none of the statistical analyses conducted so far (Ghysels et al , ; Haelermans et al , ) have revealed any sign of transfer. At the starting point of any experiment, the pretest scores of the experiment and control groups were very similar.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Students were exposed to three experiments in a row and hence it cannot be excluded that some transfer may have occurred. However, none of the statistical analyses conducted so far (Ghysels et al , ; Haelermans et al , ) have revealed any sign of transfer. At the starting point of any experiment, the pretest scores of the experiment and control groups were very similar.…”
Section: Methodsmentioning
confidence: 92%
“…In a first experimental period, digital differentiation was offered and the main results of this experiment are reported in Haelermans et al (). In a second and third period, the same experimental group was exposed to two types of formative testing: formative testing with extensive, individualized feedback, and simple formative testing with only basic feedback (total score).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current teachers face three present-day challenges. First, teachers answer the continued call for more differentiation in education to meet the needs of both low achieving and high achieving students (Haelermans, Ghysels, and Prince, 2015) [24] . In past classrooms, teachers taught to the average population with a current shift to bridge the learning gaps between these two groups.…”
Section: Role Of the Teachermentioning
confidence: 99%
“…Differentiation is instruction that is tailored to the learning preferences of different learners. Research and practice have shown that Blended Learning can give teachers the flexibility to provide these types of learning environments for their students (Bakia et al, 2012;Haelermans, Ghysels, & Prince, 2015;Lips, 2010;Watson & Gemin, 2008). In these environments, technology is used to broaden students' access to content, provide multiple avenues for creative production and help scaffold the progression of work.…”
Section: Us Department Of Education (2010) Defines Individualizatiomentioning
confidence: 99%